PENGEMBANGAN MEDIA SOLAR SYSTEM PEMBELAJARAN IPA KELAS VI DI SEKOLAH DASAR : Penelitian Research and Development (R&D) - Nova Ningsih; Feby Aimima; Arlin Nilam Sharla (STKIP Subang, 2025)
This study aims to develop and determine the feasibility and effectiveness of learning media (Solar System) on the solar system material for grade VI students of SD Negeri 79 Palembang. This study uses the Research and Development (R&D) method with the ADDIE model approach which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The validation results show that the developed media obtained a feasibility score of 100% from material experts, 92.9% from media experts, and 92% from practitioners, which is included in the